FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMENSIA DI PUSKESMAS GUNTING SAGA KEC. KUALUH SELATAN KAB. LABUHAN BATU UTARA - Helfrida Situmorang (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Dementia is an acquired intellectual and memory dysfunction caused by brain disease, and is not associated with impaired levels of consciousness. The incidence of dementia increases with increasing age. After 65 years of age, the prevalence of dementia doubles every 5 years of age. Overall the prevalence of dementia in the population over 60 years of age is 5.6%. Currently, life expectancy has increased, this is expected to increase the prevalence of dementia. Worldwide, 35.6 million people have dementia with more than half (58%) living in low and middle income countries. The purpose of this study was to determine the factors associated with the incidence of dementia in the elderly at Puskesmas Gunting Saga Kec. Kualuh Selatan District Labuhan Batu Utara 2019. Research design that is descriptive correlational, namely research conducted to describe the relationship between two variables. The population of this study was the elderly in Puskesmas Gunting Saga Kec. Kualuh Selatan, Labuhan Batu Utara Regency, amounting to 150 elderly people. Sampling using purposive sampling, which is a technique that is sampling based on certain considerations such as population characteristics or characteristics that have been previously known. Collecting data with an approach to the subject and required subject characteristics, namely elderly aged> 60 years, do not experience hearing loss, willing to be respondents. Collecting data using a questionnaire instrument used by respondents. The data analysis performed was univariate analysis and bivariate analysis. know the factors associated with the incidence of dementia in the elderly. The research results obtained an overview of the physical activity of the respondents. The data illustrates that respondents in the independent physical activity category were 35 people (89.7%), 3 people (7.7%), the dependency category. The analysis results obtained from the chi square test showed that the p value was 0. .000 (<a = 0.05). The results of this study concluded that there was a relationship between physical activity and the incidence of dementia in the elderly